A modified GnRH antagonist method in combination with letrozole, cabergoline, and GnRH antagonist for PCOS: Safe and effective ovarian stimulation to treat PCOS and prevent OHSS. (25th November 2021) - Yanagihara, Yasuho; Tanaka, Atsushi; Nagayoshi, Motoi; Tanaka, Izumi; Shinohara, Rina; Fukushima, Fumihisa; Tanaka, Akihiro; Ohno, Motoharu; Yamaguchi, Takashi; Itakura, Atsuo
Abstract: Purpose: To analyze the therapeutic efficacy of a modified controlled ovarian stimulation (COS) protocol for polycystic ovary syndrome (PCOS) that does not cause ovarian hyperstimulation syndrome (OHSS) while maintaining oocyte quality. Method: This study is a retrospective cohort study of reproductive medicine at St. Mother Clinic. We analyzed ART clinical outcomes, embryonic development, and hormone levels in 175 PCOS patients treated with four COS (GnRH agonist based long protocol, Group A; GnRH antagonist protocol with HCG trigger, Group B; GnRH antagonist protocol with GnRH agonist trigger, Group C, and the modified COS group) between 2010 and 2021. Results: Of 175 patients with PCOS, 45 and 130 patients underwent 47 and 136 oocyte retrieval cycles, 75 and 250 embryo transfer cycles with the modified COS, and with conventional methods, respectively. The cumulative pregnancy rate at one trial was a significantly higher result than in Group A and higher than in Groups B and C (cumulative pregnancy rate at one trial of Group A, B, C, and modified COS: 40.0%, 54.5%, 56.3%, and 72.3%, respectively). With this method, not clinically problematic OHSS and higher clinical outcomes than in conventional methods were observed. Conclusion: This modified COS can significantly improve clinical outcomes and eliminate OHSS.